Propuesta Arquitectónica de transformación para La revitalización del Asilo Señor de los Milagros (2022)
This Project develops a transformation architectonic proposal for the re-vitalization of the Asilo Señor de los Milagros located in the town of Giron, supported by the typology of the modular architecture, focused towards the neuro-architecture.